Emerging genetic diversity among clinical isolates of SARS-CoV-2: Lessons for today - Sheikh, Javaid Ahmad; Singh, Jasdeep; Singh, Hina; Jamal, Salma; Khubaib, Mohd; Kohli, Sunil; Dobrindt, Ulrich; Rahman, Syed Asad; Ehtesham, Nasreen Zafar; Hasnain, Seyed Ehtesham (Infection, genetics and evolution, 2020)
Considering the current pandemic of COVID-19, it is imperative to gauge the role of molecular divergence in SARS-CoV-2 with time, due to clinical and epidemiological concerns. Our analyses involving molecular phylogenetics is a step toward understanding the transmission clusters that can be correlated to pathophysiology of the disease to gain insight into virulence mechanism. As the infections are increasing rapidly, more divergence is expected followed possibly by viral adaptation. We could identify mutational hotspots which appear to be major drivers of diversity among strains, with RBD of spike protein emerging as the key region involved in interaction with ACE2 and consequently a major determinant of infection outcome. We believe that such molecular analyses correlated with clinical characteristics and host predisposition need to be evaluated at the earliest to understand viral adaptability, disease prognosis, and transmission dynamics.